Muamalah Terlarang: Maysir dan Gharar - Evan Hamzah Muchtar (STAI Asy-Syukriyyah, 2017)
Islam has constrained the freedom to engage in business and financial transactions on the basic of a number of prohibitions, ethics and norms. The prohibitions that we shall discuss here are Maisir and Gharar. As a rule, Islamic Law does not recognize transactions that have proven illegitimate factor and/or object. for that purpose, Shari'ah has identified some elements which are to be avoided in commerce or business transaction. in this regard. the prohibition of Maisir and Gharar is the most stretegic factor that defines invalid and voidable contracts and demarcates the overall limits which should not be crossed. Gharar refers to the uncertainty or hazard caused by lack of clarity regarding the subject matter or the price in a contract or exchange. Maisir refers to easily available wealth or acquisition of wealth by chance, whether or not it deprives the others right.